An effort to develop accessible tourism in Greece and Turkey: the MEDRA project approach. Issue 1 (14th March 2016) - Naniopoulos, Aristotelis; Tsalis, Panagiotis; Nalmpantis, Dimitrios
Abstract : Purpose: The purpose of this paper is to develop accessible tourism in two areas of Greece and Turkey. The areas of Drama in Greece and Mersin in Turkey have cooperated in the frame of MEDRA project to assess their potential and set up a plan for developing accessible tourism. Design/methodology/approach: The choice of the two areas was not random. Mersin currently enjoys continuous development, as one of Turkey's biggest ports and a free trade zone. Drama is a developing area in agricultural manufacturing and high-tech sectors with a rich physical environment which aspires to develop a healthy alternative tourism industry. Findings: The findings include, amongst others, the identification of needs of tourists with disabilities, and the relevant historical evolution, legislative framework, international good practices, policy-improvement proposals, accessibility assessment in Mersin and Drama, and suggestions for developing accessible infrastructure together with the training of stakeholders. Practical/implications: Greece although made a lot of progress regarding the issues of disability and accessibility still is not on the same level as many European countries, while Turkey has a lot to learn in order to deal with accessibility from a holistic point of view. Social/implications: Both countries owe a large percentage of their national income, to the tourist industry and seek ways to gain advantages in this highly competitive sector. Originality/value: The successful implementation of the MEDRA project constitutes an example worthy of a wider application in the development of accessible tourism, not only in the two countries but also to countries with similar characteristics.